Evaluasi Kesesuaian Lahan Untuk Tanaman Kopi Arabika (Coffea Arabica) di Kecamatan Pollung Kabupaten Humbang Hasundutan - Purba, Irvan Selamat; Marbu, Posma; Fauzi (Jurnal Online Pertanian Tropik, 2018)
The aims of this study was to evaluate the suitability of land for Arabica coffee crops in Pollung District of Humbang Hasundutan Regency. There are sixteen land map units (SPL) determined based on the soil type map, slope map and altitude map resulting from topographic map with scale of 1: 50.000, then grounding on soil type map data, slope map, and altitude map (overlay). Assessment of land suitability class based on the criteria from Bogor Land Research Center. The land evaluation method is the matching method. The results showed that the highest potential land suitability class on Arabica coffee plant was SPL 7 very suitable (S1) and SPL 3, 4, 5, 8, 9, 10, 12, 15, 16 suitable with marginal condition with limit factor is rooting medium (S3rc)